Anion-cation co-embedded Na2V6O16, preparation method and application thereof, and aqueous zinc ion battery

Through the Na2V6O16 method of pre-embedded anion and cation, the problem of low capacity and poor stability during the charging and discharging process of Na2V6O16 was solved, and the performance of high capacity and long cycles was achieved, which promoted the water-based zinc ion battery technology. development.

CN119263344APending Publication Date: 2025-01-07LIUPANSHUI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411632304.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the existing Na2V6O16 preparation technology, the immersion method has problems such as low capacity, fast attenuation and poor stability during the charging and discharging process, which affects the practical application performance of aqueous zinc ion batteries.

Method used

By using the method of co-pre-embedding of anion and cations, V2O5 is mixed with sodium and phosphorus salts and impregnated and dried to prepare Na+, PO43-, SO42-, F-, Cl-, I-, Br-pre-embedding of Na+, PO43-, SO42-, F-, Cl-, I-, and Br-pre-embedding Na2V6O16 optimizes the channel for zinc ions to be embedded and disengaged, buffers the volume changes during charging and discharging, and improves the ion diffusion rate and structural stability.

Benefits of technology

The zinc ion battery achieved high capacity and long cycle stability showed excellent electrochemical performance, including high specific capacity and significantly improved cycle stability. The battery capacity reached 355mAh/g at a current density of 0.2A/g, 4.0 The capacity retention rate of 4000 cycles under A/g current density is 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263344A_ABST
    Figure CN119263344A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of zinc ion batteries, and provides an anion-cation co-embedded Na2V6O16, a preparation method and application thereof and an aqueous zinc ion battery, V2O5 and an anion-cation solution are mixed, impregnated and dried to obtain the anion-cation co-embedded Na2V6O16; na2V6O16 in which Na < + >, PO4 < 3-> and SO4 < 2-> (or SO3 < 2->, F <->, Cl <->, I <-> and Br <->) are pre-embedded is prepared by using a one-step impregnation method, and pre-embedded cations and anions can better strengthen a vanadium-oxygen structure and optimize a zinc ion embedding and removing channel, so that the Na2V6O16 structural phase change in the zinc ion embedding and removing process is less, and the side reaction is less; positive ions and negative ions are embedded between vanadium oxide layers or in a tunnel structure in advance, so that the volume change in the charge-discharge process can be effectively buffered, the ion diffusion rate is improved, and the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc ion batteries, and in particular to a Na2V6O 16 Its preparation method and application and aqueous zinc ion battery. Background Art

[0002] Under the dual challenges of global energy crisis and environmental pollution, it is particularly urgent to develop new and efficient energy storage systems. Aqueous zinc-ion batteries (Zinc-ion batteries, ZiBs) have become an important candidate for the next generation of energy storage technology due to their low cost, high safety, environmental friendliness, high theoretical capacity and stable chemical properties of zinc.

[0003] In the research of aqueous zinc-ion batteries, vanadium-based materials have shown great potential as positive electrode materials due to their layered structure and multivalent properties. In particular, Na2V6O 16 , due to its high theoretical capacity and unique ion diffusion channels, it is considered to be an ideal candidate for cathode materials in aqueous zinc-ion batteries.

[0004] Jae Su Yu et al. [10.1016 / j.cej.2023.146777] used NH4VO3, NaC 12 H 25 Se-embedded Na2V6O was prepared by hydrothermal reaction at 200℃ for 10h and calcination at 350℃ in nitrogen atmosphere using SO4, C3H5NO and H2SeO3 as raw materials. 16 The assembled zinc-ion battery has a specific capacity of 329.15 mAh / g at a current density of 2 A / g, and a capacity of 146.86 mAh / g after 5000 cycles at a current density of 2 A / g, with a capacity retention rate of 70.75%.

[0005] Linyu Yang et al. [10.1039 / d2ce00609j] used V2O5 and CH3COONa as raw materials and prepared Na2V6O by immersion at 25℃ for 90h. 16 ·1.96H2O nanorods, the assembled zinc ion battery has a specific capacity of 366.8mAh / g at a current density of 0.3A / g, and a capacity of 268.3mAh / g after 1000 cycles at a current density of 3A / g, with a capacity retention rate of 86.6%.

[0006] Liqiang Mai et al. [10.1021 / acs.nanolett.7b04889] prepared Na2V6O by using V2O5 and NaOH as raw materials through hydrothermal reaction at 180℃ for 24h and calcination at 400℃ in air atmosphere for 3h. 16·1.63H2O, the specific capacity of the assembled zinc ion battery reached 352mAh / g at a current density of 0.05A / g, and the capacity was 140mAh / g after 6000 cycles at a current density of 5A / g, with a capacity retention rate of 90%.

[0007] Hao Jia et al. [10.1016 / j.ensm.2021.11.018] used V2O5 and NaOH as raw materials and prepared Na2V6O by hydrothermal reaction at 180℃ for 24h. 16 ·1.63H2O, the specific capacity of the assembled zinc ion battery reached 300mAh / g at a current density of 0.1A / g, and the capacity was 84mAh / g after 1200 cycles at a current density of 1A / g, with a capacity retention rate of 78.5%.

[0008] Mingshan Wang et al. [10.1002 / smll.202405139] used V2O5 and NaCl as raw materials and stirred and impregnated them at room temperature for 72 hours to prepare Na2V6O 16 ·1.5H2O, the specific capacity of the assembled zinc ion battery reached 270mAh / g at a current density of 0.1A / g, and the capacity was 150mAh / g after 1000 cycles at a current density of 1A / g, with a capacity retention rate of 71.0%.

[0009] Esther S.Takeuchi et al. [10.1021 / acs.chemmater.9b05103] used V2O5 and NaOH as raw materials and stirred and impregnated them at 50°C in a nitrogen atmosphere for 3 h to prepare Na2V6O 16 ·2H2O, and then calcined at 500℃ for 3h in air atmosphere to obtain Na 1.25 V3O8, the zinc ion batteries assembled with the two materials have a specific capacity of 320mAh / g and 150mAh / g at a current density of 0.1A / g, and the capacities are 285mAh / g and 60mAh / g after 50 cycles at a current density of 0.5A / g, and the capacity retention rates are 89.6% and 40%, respectively.

[0010] Yu-Kuei Hsu et al. [10.1021 / acsami.2c22728] used NH4VO3 and Na2SO4 as raw materials to prepare an electrodeposition solution, with activated carbon cloth as the substrate, at 70°C and 2 mA / cm 2 The Na2V6O 16 ·3H2O NBs / ACC, the assembled zinc ion battery has a specific capacity of 210 mAh / g at a current density of 0.1 A / g, and a capacity of 3.5 mAh / cm after 200 cycles at a current density of 0.1 A / g 2, the capacity retention rate is 71.4%.

[0011] Vaiyapuri Soundharrajan et al. [10.1021 / acs.nanolett.7b05403] prepared Na2V6O by using V2O5 and NaF as raw materials to prepare a mixed solution by microwave reaction at 200℃ for 0.5h. 16 ·3H2O, the specific capacity of the assembled zinc ion battery reached 275mAh / g at a rate of 2C, and the capacity was 250mAh / g after 400 cycles at a rate of 5C, with a capacity retention rate of 91.0%.

[0012] Ying Bai et al. [10.1021 / acsenergylett.2c01890] prepared Na2V6O by using V2O5, NaOH and H2O2 as raw materials to prepare the reaction solution through hydrothermal reaction at 200℃ for 24h. 16 ·3H2O, the specific capacity of the assembled zinc ion battery reached 500mAh / g at a current density of 0.1A / g, and the capacity was 210mAh / g after 5000 cycles at a current density of 20A / g, with a capacity retention rate of 70.6%.

[0013] Fang Hu et al. [10.1016 / j.jechem.2019.03.036] used NH4VO3, NaOH, Na2CO3 and H2O2 as raw materials to prepare the reaction solution, and prepared Na2V6O by hydrothermal reaction at 200℃ for 24h. 16 ·2.14H2O, the specific capacity of the assembled zinc ion battery reached 466mAh / g at a current density of 0.1A / g, and the capacity was 210mAh / g after 2000 cycles at a current density of 20A / g, with a capacity retention rate of 90%.

[0014] Liping Qin et al. [10.1016 / j.mtcomm.2022.103460] used V2O5 and NaOH as raw materials to prepare the reaction solution, and prepared Na2V6O by hydrothermal reaction at 200℃ for 36h. 16 ·1.66H2O, the assembled zinc ion battery has a specific capacity of 400mAh / g at a current density of 0.5A / g, and a capacity of 100mAh / g after 1800 cycles at a current density of 5A / g, with a capacity retention rate of 98%.

[0015] Existing Na2V6O 16 Preparation techniques include impregnation, hydrothermal, and electrodeposition. The impregnation method is widely used due to its simple operation and easy scalability. However, due to the volume expansion and ion migration during the charge and discharge process, the Na2V6O prepared by the impregnation method has a high 16In practical applications, it faces problems such as low capacity, rapid attenuation and poor stability. Summary of the invention

[0016] The purpose of the present invention is to overcome the problems in the prior art and provide a Na2V6O 16 Its preparation method and application and aqueous zinc ion battery.

[0017] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0018] The present invention provides a kind of Na2V6O pre-embedded with anions and cations 16 The preparation method comprises the following steps:

[0019] The V2O5 and anion and cation solutions are mixed, impregnated, and dried to obtain the Na2V6O pre-embedded with anions and cations. 16 ;

[0020] The anion and cation solution comprises sodium salt, phosphate salt and water.

[0021] Preferably, the sodium salt is NaF, NaCl, NaBr, NaI, Na2SO3 or Na2SO4; the phosphate salt is Na3PO4, Na2HPO4 or NaH2PO4.

[0022] Preferably, the concentration of sodium in the anion and cation solution is 5 to 30 g / L, and the concentration of phosphorus is 1 to 2 g / L.

[0023] Preferably, the mass ratio of V2O5 to water is 1:40-90.

[0024] Preferably, the immersion temperature is 0-30° C., the rotation speed is 200-450 rpm, and the time is 10-100 h.

[0025] Preferably, the drying temperature is 60-110° C. and the drying time is 5-10 hours.

[0026] The present invention also provides the anion-cation co-pre-embedded Na2V6O 16 The anion-cation co-embedded Na2V6O prepared by the preparation method 16 .

[0027] The present invention also provides the anion-cation co-pre-embedded Na2V6O 16 Application in aqueous zinc-ion batteries.

[0028] The present invention also provides an aqueous zinc ion battery, wherein the conductive paste of the aqueous zinc ion battery comprises the anion-cation co-embedded Na2V6O 16, conductive agents and adhesives;

[0029] Anion-cation co-preintercalated Na2V6O 16 The loading amount on the substrate is 2-7 mg / cm 2 .

[0030] Preferably, the anion and cation are co-pre-embedded in Na2V6O 16 , the mass ratio of conductive agent to binder is 7~8:1~2:1.

[0031] The present invention provides a kind of Na2V6O pre-embedded with anions and cations 16 The preparation method of Na + PO4 3- 、SO4 2- (or SO3 2- 、F - , Cl - ,I - Br - )Total pre-embedded Na2V6O 16 The pre-embedded cations and anions can better strengthen the vanadium oxide structure and optimize the channels for zinc ion embedding and extraction, making the zinc ion embedding and extraction process Na2V6O 16 There are fewer structural phase changes and fewer side reactions. Moreover, pre-embedding cations and anions between vanadium oxide layers or in tunnel structures can effectively buffer volume changes during charge and discharge, increase the ion diffusion rate, and thus enhance the electrochemical performance of the material. The structural stability is enhanced through the interaction between cations and anions, achieving the dual advantages of high capacity and long cycle stability.

[0032] The present invention also provides an aqueous lithium ion battery, wherein the anions and cations of the present invention are co-embedded in Na2V6O 16 The conductive slurry is coated on a substrate and used as an aqueous zinc ion positive electrode material to assemble into a button battery. A zinc ion battery with high capacity and long cycle stability can be obtained, which exhibits excellent electrochemical properties, including high specific capacity, excellent rate performance and significantly improved cycle stability.

[0033] After experiments, the battery capacity reached 355mAh / g at a current density of 0.2A / g, and the battery capacity retention rate was 100% after 4000 cycles at a current density of 4.0A / g. It is expected to promote the development and application of aqueous zinc ion battery technology, and the method of the present invention is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a cycle specific capacity diagram of the button battery assembled with the aqueous zinc ion positive electrode material in Example 1. DETAILED DESCRIPTION

[0035] The present invention provides a kind of Na2V6O pre-embedded with anions and cations 16 The preparation method comprises the following steps:

[0036] The V2O5 and anion and cation solutions are mixed, impregnated, and dried to obtain the Na2V6O pre-embedded with anions and cations. 16 ;

[0037] The anion and cation solution comprises sodium salt, phosphate salt and water.

[0038] In the present invention, the sodium salt is NaF, NaCl, NaBr, NaI, Na2SO3 or Na2SO4; the phosphate salt is Na3PO4, Na2HPO4 or NaH2PO4.

[0039] In the present invention, the concentration of sodium in the anion and cation solution is preferably 5-30 g / L, more preferably 10-25 g / L, and more preferably 15-20 g / L; the concentration of phosphorus is preferably 1-2 g / L, more preferably 1.2-1.8 g / L, and more preferably 1.4-1.6 g / L.

[0040] In the present invention, the mass ratio of V2O5 to water is preferably 1:40-90, more preferably 1:50-80, and even more preferably 1:60-70.

[0041] In the present invention, the immersion temperature is preferably 0-30°C, more preferably 5-25°C, more preferably 10-20°C; the rotation speed is preferably 200-450rpm, more preferably 250-400rpm, more preferably 300-350rpm; the time is preferably 10-100h, more preferably 20-80h, more preferably 40-60h.

[0042] In the present invention, solid-liquid separation is performed after the impregnation is completed, and the obtained solid product is dried.

[0043] In the present invention, the drying temperature is preferably 60 to 110° C., more preferably 70 to 100° C., and more preferably 80 to 90° C.; the drying time is preferably 5 to 10 h, more preferably 6 to 9 h, and more preferably 7 to 8 h.

[0044] The present invention also provides the anion-cation co-pre-embedded Na2V6O 16 The anion-cation co-embedded Na2V6O prepared by the preparation method 16 .

[0045] The present invention also provides the anion-cation co-pre-embedded Na2V6O 16Application in aqueous zinc-ion batteries.

[0046] The present invention also provides an aqueous zinc ion battery, wherein the conductive paste of the aqueous zinc ion battery comprises the anion-cation co-embedded Na2V6O 16 , conductive agent and adhesive.

[0047] In the present invention, the anion and cation are co-embedded in Na2V6O 16 The conductive agent and the binder are mixed to obtain a conductive paste, which is then coated on a substrate for use.

[0048] In the present invention, the anion and cation are co-pre-embedded in Na2V6O 16 The loading amount on the substrate is preferably 2-7 mg / cm 2 , more preferably 3 to 6 mg / cm 2 , more preferably 4 to 5 mg / cm 2 .

[0049] In the present invention, the conductive agent comprises one or more of carbon black, conductive graphite, carbon nanotubes and graphene; the binder comprises one or more of polyvinylidene fluoride, polyacrylate, polyvinyl alcohol, sodium carboxymethyl cellulose and polyimide; and the substrate comprises titanium foil, stainless steel foil, graphite foil, carbon paper or carbon cloth.

[0050] In the present invention, the anion and cation are co-pre-embedded in Na2V6O 16 The mass ratio of the conductive agent to the binder is preferably 7-8:1-2:1, more preferably 7.2-7.8:1.2-1.8:1, and more preferably 7.4-7.6:1.4-1.6:1.

[0051] In the present invention, the electrolyte of the aqueous zinc ion battery is preferably a zinc trifluoromethanesulfonate solution, the positive electrode is a substrate coated with a conductive slurry, the negative electrode is a zinc foil, and the separator is glass fiber.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] Na2SO4, Na3PO4 and 97.87 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 10 g / L and a P concentration of 1 g / L.

[0055] 1.09 g of V2O5 was immersed in the anion and cation impregnation solution at 15 °C and a stirring speed of 200 rpm for 10 h. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 60 °C for 10 h to obtain Na + PO4 3- 、SO4 2- Co-pre-intercalated Na2V6O 16 .

[0056] The anion and cation co-embedded Na2V6O prepared in Example 1 was added in a mass ratio of 7:2:1. 16 , carbon nanotubes and polyvinyl alcohol to obtain Na2V6O pre-embedded with anions and cations 16 Electrode slurry, the slurry is coated on titanium foil to prepare anion-cation co-pre-embedded Na2V6O 16 Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading amount is 2 mg / cm 2 ;

[0057] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16 The specific capacity of the battery with electrode material reaches 355mAh / g;

[0058] The cycle stability test was carried out at a current density of 4.0A / g. The results are as follows Figure 1 shown.

[0059] according to Figure 1 It can be found that the anion-cation co-pre-embedded Na2V6O prepared by the present invention 16 When the electrode material is used, the battery is cycled 4000 times and the battery capacity retention rate is 100%.

[0060] Example 2

[0061] Na2SO3, Na2HPO4 and 96.73 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 15 g / L and a P concentration of 1.2 g / L.

[0062] 1.21g V2O5 was immersed in the anion and cation impregnation solution at 5°C and a stirring speed of 250rpm for 20h. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 70°C for 9h to obtain Na +、HPO4 2- 、SO3 2- Co-pre-intercalated Na2V6O 16 .

[0063] The anion-cation co-embedded Na2V6O prepared in Example 2 was added in a mass ratio of 7.5:1.5:1. 16 , conductive graphite and polyvinyl alcohol are mixed to obtain Na2V6O with anion and cation co-embedded 16 Electrode slurry, the slurry is coated on a stainless steel foil to prepare anion-cation co-embedded Na2V6O 16 Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading amount is 3 mg / cm 2 ;

[0064] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16 The specific capacity of the battery of the electrode material reaches 352 mAh / g. After 4000 cycles at a current density of 4.0 A / g, the capacity retention rate of the battery is 100%.

[0065] Example 3

[0066] NaI, NaH2PO4 and 96.40 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 20 g / L and a P concentration of 1.4 g / L.

[0067] 1.38g V2O5 was immersed in the anion and cation impregnation solution at 10°C and a stirring speed of 300 rpm for 40 hours. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 80°C for 8 hours to obtain Na + 、H2PO4 - ,I - Co-pre-intercalated Na2V6O 16 .

[0068] The anion and cation co-embedded Na2V6O prepared in Example 3 was added in a mass ratio of 8:1:1. 16 , carbon black and polyvinylidene fluoride to obtain anion-cation co-pre-embedded Na2V6O 16 Electrode slurry, the slurry is coated on titanium foil to prepare anion-cation co-pre-embedded Na2V6O 16Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading amount is 4 mg / cm 2 ;

[0069] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16 The specific capacity of the battery of the electrode material reaches 350 mAh / g. After 4000 cycles at a current density of 4.0 A / g, the capacity retention rate of the battery is 99%.

[0070] Example 4

[0071] NaBr, Na3PO4 and 96.49 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 25 g / L and a P concentration of 1.6 g / L.

[0072] 1.61g V2O5 was immersed in the anion and cation impregnation solution at 0°C and a stirring speed of 350rpm for 60h. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 90°C for 7h to obtain Na + PO4 3- Br - Co-pre-intercalated Na2V6O 16 .

[0073] The anion and cation co-embedded Na2V6O prepared in Example 4 was added in a mass ratio of 7:2:1. 16 , graphene and sodium carboxymethyl cellulose were mixed to obtain Na2V6O pre-embedded with anions and cations. 16 Electrode slurry, the slurry is coated on carbon paper to prepare anion and cation co-embedded Na2V6O 16 Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading amount is 5 mg / cm 2 ;

[0074] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16The specific capacity of the battery of the electrode material reaches 348 mAh / g. After 4000 cycles at a current density of 4.0 A / g, the capacity retention rate of the battery is 99%.

[0075] Example 5

[0076] NaCl, Na2HPO4 and 96.03 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 30 g / L and a P concentration of 1.8 g / L.

[0077] 1.92g V2O5 was immersed in the anion and cation impregnation solution at 20°C and a stirring speed of 400rpm for 80h. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 100°C for 6h to obtain Na + 、HPO4 2- , Cl - Co-pre-intercalated Na2V6O 16 .

[0078] The anion-cation co-embedded Na2V6O prepared in Example 5 was added in a mass ratio of 7.5:1.5:1. 16 , carbon black and polyimide were mixed to obtain Na2V6O pre-embedded with anions and cations. 16 Electrode slurry, the slurry is coated on carbon cloth to prepare anion and cation co-embedded Na2V6O 16 Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading amount is 6 mg / cm 2 ;

[0079] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16 The specific capacity of the battery of the electrode material reaches 348 mAh / g. After 4000 cycles at a current density of 4.0 A / g, the capacity retention rate of the battery is 98%.

[0080] Example 6

[0081] NaF, NaH2PO4 and 99.42 mL of deionized water were mixed and dissolved to obtain anion and cation impregnation solutions with a Na concentration of 5 g / L and a P concentration of 2 g / L.

[0082] 2.45g V2O5 was immersed in the anion and cation impregnation solution at 30°C and a stirring speed of 450rpm for 100h. After the reaction was completed, the solid-liquid separation was performed and the solid product was vacuum dried at 110°C for 5h to obtain Na + 、H2PO4 - 、F - Co-pre-intercalated Na2V6O 16 .

[0083] The anion and cation co-embedded Na2V6O prepared in Example 6 was added in a mass ratio of 8:1:1. 16 , conductive graphite and polyacrylate were mixed to obtain Na2V6O pre-embedded with anions and cations. 16 Electrode slurry, the slurry is coated on a graphite foil to prepare anion-cation co-pre-embedded Na2V6O 16 Electrode material: Na2V6O with anion and cation co-embedded 16 Na2V6O with anions and cations co-embedded in electrode materials 16 The loading capacity is 7 mg / cm 2 ;

[0084] 2 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, and the anions and cations were co-embedded in Na2V6O 16 The electrode material is the positive electrode, the zinc foil is the negative electrode, and the glass fiber is used as the separator to assemble the button battery; at a current density of 0.2A / g, the Na2V6O 16 The specific capacity of the battery with electrode material reaches 346mAh / g. After 4000 cycles at a current density of 4.0A / g, the capacity retention rate of the battery is 98%.

[0085] From the above examples, it can be seen that the present invention provides Na2V6O pre-embedded with anions and cations. 16 After being prepared into electrode slurry, the battery capacity reaches 355mAh / g at a current density of 0.2A / g, and the battery capacity retention rate is 100% after 4000 cycles at a current density of 4.0A / g; it is expected to promote the development and application of aqueous zinc-ion battery technology.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Anion-cation co-pre-embedded Na2V6O 16 The preparation method is characterized in that It includes the following steps: The V2O5 and anion and cation solutions are mixed, impregnated, and dried to obtain the Na2V6O pre-embedded with anions and cations. 16 ; The anion and cation solution comprises sodium salt, phosphate salt and water.

2. The anion-cation co-pre-embedded Na2V6O as claimed in claim 1 16 The preparation method is characterized in that The sodium salt is NaF, NaCl, NaBr, NaI, Na2SO3 or Na2SO4; the phosphate salt is Na3PO4, Na2HPO4 or NaH2PO4.

3. The anion-cation co-pre-embedded Na2V6O as claimed in claim 1 or 2 16 The preparation method is characterized in that The concentration of sodium element in the anion and cation solution is 5-30 g / L, and the concentration of phosphorus element is 1-2 g / L.

4. The anion-cation co-pre-embedded Na2V6O as claimed in claim 3 16 The preparation method is characterized in that The mass ratio of V2O5 to water is 1:40-90.

5. The anion-cation co-pre-embedded Na2V6O as claimed in claim 1 or 4 16 The preparation method is characterized in that The immersion temperature is 0-30° C., the rotation speed is 200-450 rpm, and the time is 10-100 hours.

6. The anion-cation co-pre-embedded Na2V6O as claimed in claim 5 16 The preparation method is characterized in that The drying temperature is 60-110° C. and the drying time is 5-10 hours.

7. The anion-cation co-pre-embedded Na2V6O according to any one of claims 1 to 6 16 The anion-cation co-embedded Na2V6O prepared by the preparation method 16 .

8. The anion-cation co-pre-embedded Na2V6O according to claim 7 16 Application in aqueous zinc-ion batteries.

9. An aqueous zinc ion battery, characterized in that: The conductive paste of the aqueous zinc ion battery comprises the anion-cation co-embedded Na2V6O 16 , conductive agents and adhesives; Anion-cation co-preintercalated Na2V6O 16 The loading amount on the substrate is 2-7 mg / cm 2 .

10. The aqueous zinc ion battery according to claim 9, characterized in that: The anions and cations are co-pre-embedded in Na2V6O 16 , the mass ratio of conductive agent to binder is 7~8:1~2:1.